Evaluation of radiation exposure in open dental clinics using thermoluminescence dosimeters and questionnaires - Bahija T Basheer; Renad I Allahim; Samar S Alarfaj; Tala A Alkharashi; Amal A Fallatah; Amerah S Alqahtani; Shuruq S Aljarallah (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of this study was to evaluate radiation exposure in dental open clinics in King Saud Bin Abdulaziz University for Health Sciences (KSAU-HS) using thermoluminescence dosimeters (TLDs) to check if it exceeds the annual assigned exposure limit and to assess students' practices regarding radiation protection measures and their knowledge regarding the application of digital remote-control settings and TLDs. Materials and Methods: This pilot institutional-based observational study was conducted among the clinical year students and interns at KSAU-HS College of Dentistry open clinical areas using TLDs and questionnaires. Sixteen lithium fluoride TLDs (TLD-100) were distributed evenly in the clinical areas occupied by clinical year dental students and interns for 24 working days from September 15 to October 20, 2019. Each TLD was labeled with a serial number and fixed at the assigned clinic of each specialty. The TLDs were placed in a zigzag manner at the right corner of the selected clinic to prevent overlapping of the area coverage by each dosimeter. Results: The mean monthly TLD readings were found to be 69.265 uSv with a higher mean value in the female clinical area (74.2975 uSv) than the male clinical area (64.234 uSv). Taking into account the 8 months of clinical exposure during the academic year, the expected annual radiation exposure would be 0.554 mSv which is significantly lower than the annual limit of radiation exposure recommended by the International Commission on Radiological Protection, i.e., 1 mSv. Conclusion: TLD readings concluded that radiation exposure was within safe limits with an estimation of 0.544 mSv per year. However, students require further education regarding protective and safety measures and the utilization of radiation equipment. Clinical Significance: The lack of studies regarding the amount of radiation exposure from dental imaging and the safety of intraoral radiographic machines present in open clinics in any educational institute necessitates conducting this kind of study.